The medical act in distorsion: relation no doctor no patient. Displacement of the power of decision to the group family-media-client state - Muravchik, Claudia (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2016)
The relation doctor-patient has been developing: since the medical hegemony to the empowerish of the patient and since the mentioned binomial to the incorporation of others involved(Interdisciplinary team, family, friends, legal councellors). We shoud refer (even more when the case involves pediatric patients or incapables) to the relation treating team family and its social context. There are 2 cases described that result paradigmatic to illustrate what would be a displacement of the gravitacional axis of power inside this relation and the appearance of a new hegemony. This hegemony would be represented for the family that throughout power relations established with politicians and media and built over the illness of the patient decides over the therapeutic measures to implement based in íts own priorities. This results into some benefits for the relatives, without being profitable in real benefits for the patient and that in extreme cases, it results in therapeutic cruelty.